when is the sum of squares a power of a prime??

แชร์
ฝัง
  • เผยแพร่เมื่อ 4 ก.พ. 2025

ความคิดเห็น • 48

  • @goodplacetostop2973
    @goodplacetostop2973 3 ปีที่แล้ว +53

    16:41 Happy New Year everyone! May 2022 be full of high energies and greater focus for you to study and make your dreams a reality.

  • @suhail_69
    @suhail_69 3 ปีที่แล้ว +6

    Thank you for putting together such amazing videos. Happy new year Mike!

  • @kevinmartin7760
    @kevinmartin7760 3 ปีที่แล้ว +29

    This problem expands into an irritatingly large number of cases...

    • @sleepycritical6950
      @sleepycritical6950 3 ปีที่แล้ว +3

      That's maths. I've been very sloppy with my proofs because of this.

  • @ivankaznacheyeu4798
    @ivankaznacheyeu4798 3 ปีที่แล้ว +14

    Checking of n=14 case is incorrect, according to previous calculations product (n-1)(2n^2+5n+6) is divisible by 6 for any natural n.

    • @davidgould9431
      @davidgould9431 3 ปีที่แล้ว +11

      You're right. (n-1)(2n² + 5n + 6) = (13)(2∙196 + 70 + 6) = (13)(468) = 2²∙3²∙13² which is divisible by 6 but clearly isn't a power of a prime.

  • @Ahmed-Youcef1959
    @Ahmed-Youcef1959 3 ปีที่แล้ว +1

    happy new year everybody

  • @superhightemperature2941
    @superhightemperature2941 3 ปีที่แล้ว +4

    Happy New Year everybody!

  • @noumanegaou3227
    @noumanegaou3227 3 ปีที่แล้ว +7

    We have a good idea how to start 2022. You publishe a wormap problem and we send our solution And you're showing one of the right solutions in the last video.

  • @jakeb6977
    @jakeb6977 3 ปีที่แล้ว +4

    n=2 is the easy solution since it means p and k are equal to 2 as well

  • @alainbarnier1995
    @alainbarnier1995 3 ปีที่แล้ว +2

    Hard this one ! Happy new year :)

  • @andrewkarsten5268
    @andrewkarsten5268 3 ปีที่แล้ว +1

    The associated prime with the n=7 case is 139. Since at n=4, sum=29, we have sum=29+25=54 for n=5, sum=54+36=90 for n=6, and lastly sum=90+49=139 for the n=7 case, and 139 is a prime.

  • @krisbrandenberger544
    @krisbrandenberger544 3 ปีที่แล้ว +1

    For the n=14 case, the left hand side should be 6084 and the right hand side should be 36 × 13².

  • @HagenvonEitzen
    @HagenvonEitzen 3 ปีที่แล้ว

    One can exploit n-1 < 2n^2+… earlier and write n-1 = ap^x, 2n^2+… = bp^y with ab=6, x+y=k>0. In fact, we even have 2n^2+… > (n-1)^2. So bp^y>a^2p^(2x). If 2x>y, we must have p

  • @particleonazock2246
    @particleonazock2246 3 ปีที่แล้ว +2

    Yes, summations are oddly the only thing I can solve. I feel so euphoric.

  • @HagenvonEitzen
    @HagenvonEitzen 3 ปีที่แล้ว

    One can stumble over the factor (n-1) also by noting that n=1 makes the dum the empty sum.

  • @Hyakurin_
    @Hyakurin_ 3 ปีที่แล้ว +6

    If gcd(...)=1 one could also note that p^k does not divide n-1, since p^k>1+1+...+1=n-1, so p^k must divide the other factor (since they are relatively prime), this implies that 2n^2+5n+6=qp^k, therefore (n-1)q=6, that is n-1 divides 6.

  • @yahyaelkarkouri3117
    @yahyaelkarkouri3117 3 ปีที่แล้ว +7

    (7,139)

  • @lox7182
    @lox7182 3 ปีที่แล้ว

    I find the fact that you use sub-subcases pretty cool

  • @natepolidoro4565
    @natepolidoro4565 3 ปีที่แล้ว +4

    n=7 gives prime 139

  • @tinafeyalien
    @tinafeyalien 3 ปีที่แล้ว +1

    Not everyday you hear a maths professor repeatedly referring to factors of a prime! He means prime power.

  • @joaovictormelo6442
    @joaovictormelo6442 3 ปีที่แล้ว

    How do we know that k needs to be 1?

  • @minwithoutintroduction
    @minwithoutintroduction 3 ปีที่แล้ว +1

    16:43

  • @lyrimetacurl0
    @lyrimetacurl0 3 ปีที่แล้ว

    Here the sum of squares is excluding m=1 for some reason?
    When 1 is included you get an interesting result that sum of squares is only a power of 2 when n=24 (if n>1). Not tried it for other powers.

  • @threstytorres4306
    @threstytorres4306 3 ปีที่แล้ว +7

    58SECONDS LATE
    EDIT:
    IF N=7, THE SUM FROM M=2 UP TO 7 OF M² IS 139, WHICH IS A PRIME NUMBER
    IF N=27, THE SUM FROM M=2 UP TO 27 OF M² IS 6929, WHICH IS NOT THE SOLUTION SINCE 6 ISN'T DIVISIBLE ON 6929
    IF N=40

  • @n8cantor
    @n8cantor 3 ปีที่แล้ว

    Far too many cases!
    I found it easier to note that p cannot divide both (n-1) and (2n^2+5n+6) unless p=13 because if n ≡ 1 mod p [i.e. p divides n-1], then 2n^2+5n+6 ≡ 13 mod p, which is only congruent to 0 if p = 13.
    If p divides only one of them, then we have the cases n = 2, 3, 4, and 7 like in the video. (And as shown in the video, p^k cannot divide n-1 because then 2n^2+5n+6 1 then the bracketed term ≡ 1 mod 13, and so does not divide 13^k, so must divide 6, but it is far too large to do so.
    If x = 1, then the bracketed term is still too large to divide solely the 6, and so it must have a factor of 13. The term reduces to 9a+1≡ 0 mod 13, and solving for a gives a ≡ 10. But a can only equal 1, 2, 3, or 6 and thus there are no solutions.

  • @siyuanhuo7301
    @siyuanhuo7301 3 ปีที่แล้ว +1

    7 works, 27 fails, 40 fails, 79 fails

  • @ashokhaldar9296
    @ashokhaldar9296 3 ปีที่แล้ว

    Wow,easy to solve

  • @tomholroyd7519
    @tomholroyd7519 3 ปีที่แล้ว

    What's on your t-shirt?

    • @chandranichaki9580
      @chandranichaki9580 3 ปีที่แล้ว

      Watch the latest video of wishing happy new year in the language of Mathematics
      th-cam.com/video/lqVEgVea4Dg/w-d-xo.html 😊

  • @trueriver1950
    @trueriver1950 3 ปีที่แล้ว +1

    Answer: always.
    I think a more interesting question might have been to ask when is it an *integer* power of a prime.

  • @charlesglidden557
    @charlesglidden557 3 ปีที่แล้ว

    Case 14 is 6084
    not 5317

  • @dougforkes563
    @dougforkes563 3 ปีที่แล้ว

    Let n=x+1, substitute to get
    x(2x^2 + 9x + 13) = 6p^k
    i.e. x = ap^c
    and 2x^2 + 9x + 13 = bp^d
    where ab = 6 and c + d = k
    if c = 0 then x = 1, 2, 3, or 6 and can be tested by hand.
    1, 2, and 3 all succeed by cumulatively summing 4, 9, and 16. Plugging x=6 into formula
    gives 6(72 + 54 + 13) = 6*139 and 139 is clearly relatively prime to 2, 3, 5, 7, and 11 and thus prime.
    First four cases all succeed.
    if c = 1 or more, then substitute x = ap^c into 2x^2 + 9x + 13 to get
    2a^2 p^2c + 9ap^c + 13 which has remainder of 13 when divided by p.
    Thus p must be 13.
    Also c cannot exceed 1 or the above expression has a factor with a remainder of 1
    when divided by 13,
    Thus there may be four more cases: p=13, c=1, and a=1, 2, 3, or 6.
    We require that 9ap + p be divisible by p^2 ie 9a + 1 be divisible by p (where p is 13)
    But that is not the case for a = 1, 2, 3, 6 so these cases fail.

  • @yoavbd123
    @yoavbd123 3 ปีที่แล้ว +3

    Not related to this vid, but I recall a video that showed that if in a sequence the limit of an+1 - an = 0 , then the limit an/ n is 0
    Does anyone remember that vid and can share a link?
    Thanks!

    • @ssttaann11
      @ssttaann11 3 ปีที่แล้ว +1

      You can set b_n = n (strictly increasing and approaching +\infty). Then b_{n+1}-b_n = 1.

    • @nemoumbra0
      @nemoumbra0 3 ปีที่แล้ว +2

      @@ssttaann11 What do you mean? Is your answer related to the comment you've answered to?

    • @schweinmachtbree1013
      @schweinmachtbree1013 3 ปีที่แล้ว +1

      @@nemoumbra0 with a_n arbitrary and b_n = n you can apply the Stolz-Cesaro theorem which is the discrete version of L'Hopital's rule - it states that if the limit of (a_{n+1}-a_n)/(b_{n+1}-b_n) exists then the limit of a_n/b_n also exists and has the same value (provided that b_n satisfies a certain condition). Michael has done a video on this theorem, but probably OP wants a different video on this special case (b_n = n).

    • @chandranichaki9580
      @chandranichaki9580 3 ปีที่แล้ว

      Watch the latest video of wishing happy new year in the language of Mathematics
      th-cam.com/video/lqVEgVea4Dg/w-d-xo.html 😊😊

    • @TheEternalVortex42
      @TheEternalVortex42 2 ปีที่แล้ว

      Simple proof:
      Take ε > 0 then for n ≥ N we have a_{n+1} - a_n < ε
      Now simply take a sum of both sides from N to n
      ∑ a_n - a_{n-1} < ∑ ε
      This sum telescopes, so
      a_n - a_{N-1} < (n - N + 1) ε < n ε
      Now just divide by n
      a_n / n < ε + a_{N-1}/n
      But the last term clearly ⭢ 0 since a_{N-1} is a constant. So we are done.
      (I didn't write it out, but you also need the other inequality for -ε but it's exactly the same).

  • @leif1075
    @leif1075 3 ปีที่แล้ว +1

    Wyy would anyone think to rewrite the sum of squares as n minus 1 times something..surely you can solve by keeping it in its original form?

  • @BiscuitZombies
    @BiscuitZombies 3 ปีที่แล้ว

    test

  • @daneeko
    @daneeko 3 ปีที่แล้ว +1

    whaaaaaat